Development and Characterization of Mikania, Kapok, Wool, Sugarcane, and Pineapple Fiber Reinforced Polyester Composite - Rafid Anan; Hasan Al Mahmud; Tabriz Ahnaf Khan; Md Sakib Ul Alam Sakib; Md Shahadhat Hossain (Engineering Reports)
ABSTRACT This study utilizes plant‐derived fibers including Mikania, wool, kapok, sugarcane, and pineapple as strengthening additions to fabricated and tested reinforced polyester mixtures. This study aimed to examine the mechanical qualities and potential applications of these natural materials in boosting the effectiveness of polyester composites. The composites were formed by including natural fibers into a polyester base using a hand lay‐up preparation method. The finished samples received a complete assessment, covering tensile and impact testing as well as SEM analysis. The findings showed that incorporating natural materials like Mikania vines, wool, kapok fuzz, sugarcane fibers, and pineapple leaves had a notably positive effect on the mechanical features of the plastic composites. The tensile strength of the material combined pineapple was particularly high, achieving a maximum stress of 42.4822 N/mm2 and a maximum stretch of 4.27950%. Similarly, that same composite exhibited a maximum stretch of 3.75753% and a maximum stress of 77.4922 N/mm2 during the bending experiment. The substances exhibiting the strongest impact endurance, as determined by the impact assessment, included kapok, Mikania, wool, pineapple, and sugarcane. The kapok provided an impact toughness of 1.2 N m, which was somewhat elevated. This research offers a precious understanding of using natural fibers as strengthening additives in polyester composites, demonstrating their flexible perspective for many uses. The discoveries present hopeful possibilities for additional examination and progression in composite materials, consequently advancing the development of sustainable materials.